Laparoscopic gastrectomy with lymph node dissection for the treatment of remnant stomach gastrointestinal stromal tumors in incomplete-type Carney’s triad: a case report - Yuhi Shimura; Shingo Kanaji; Naoki Urakawa; Masashi Yamamoto; Masako Utsumi; Gousuke Takiguchi; Hiroshi Hasegawa; Yoshiko Matsuda; Kimihiro Yamashita; Takeru Matsuda; Taro Oshikiri; Tetsu Nakamura; et al. (Surgical Case Reports, 2020)
Abstract Background We report a rare case of gastrointestinal stromal tumors (GISTs) in Carney’s triad, successfully treated using laparoscopic gastrectomy with lymph node dissection after chemotherapy. Case presentation A 21-year-old woman presented to our hospital for treatment of recurrent GISTs. The patient had been admitted for treatment 11 years prior, with black stools being the chief presenting complaint at that time. On examination at that time, multiple submucosal tumors in the pyloric antrum and multiple pulmonary tumors had been observed. She underwent open partial gastrectomy, and the diagnosis of GISTs was confirmed. She was administered tyrosine kinase inhibitors to treat lung metastases from 2 months after surgery. Due to the increasing size of the lung tumors, a right upper lobectomy was performed 9 years after the index gastric surgery. Histopathological examination of the lung specimen, in combination with re-examination of the gastric specimens, was indicative of incomplete-type Carney’s triad. Eleven years after the index gastric surgery, multiple GISTs were observed in her entire stomach. Tumor biopsy revealed a succinate dehydrogenase deficiency, confirming the diagnosis of recurrent GISTs. For treatment, the patient underwent laparoscopic completion gastrectomy, with D1 plus lymph node dissection. Conclusion This is a first case report of completion gastrectomy performed laparoscopically for the treatment of GISTs associated with incomplete-type Carney’s triad. The recurrent GISTs developed over a protracted period of 11 years from the index gastric surgery to tumor recurrence.